Social partnership models challenges to IR actors - Sibal, Jorge V. (2010)
With intensifying globalization, the past and present government administrators are focused in reducing poverty and creating jobs through industry competitiveness within a labor policy regime that promotes decent work. Skills-building and education programs, infrastructure development and reduced fiscal deficit are among the government's major concerns.

This paper is a documentation of good social partnerships among the industry and labor leaders in 16 companies to demonstrate an important adjustment strategy in coping with increased competition resulting from globalization.
Keywords: Partnership (Business); International relations